ChemInform Abstract: Synthesis and Applications of 4‐Substituted 1‐(4‐Iodophenyl)pyrrolidine‐2, 5‐diones. Issue 44 (15th October 2015) - Ali, Bakhat; Shamim, Anwar; Vasconcelos, Stanley N. S.; Stefani, Helio A.
Abstract 4‐Acetoxy substituted 1‐(4‐iodophenyl)pyrrolidine‐2, 5‐dione is successfully transformed to the corresponding 4‐amino substituted derivatives.